2017
DOI: 10.22161/ijeab/2.5.16
|View full text |Cite
|
Sign up to set email alerts
|

Extraction and Quantification of Carpaine from Carica papaya Leaves of Vietnam

Abstract: Abstract-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
1
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 5 publications
0
3
1
3
Order By: Relevance
“…Carpaine alkaloid concentration was lower than Vien's study (2017) [28]. That study obtained 63% of carpaine alkaloid in the total papaya extract that showed concentration of carpaine carpaine alkaloid in this study was lower because of the geographical and climate differences in Indonesia and Vietnam, make the nutrients in the soil would be vary causing differences content of secondary metabolites.…”
Section: Discussioncontrasting
confidence: 53%
“…Carpaine alkaloid concentration was lower than Vien's study (2017) [28]. That study obtained 63% of carpaine alkaloid in the total papaya extract that showed concentration of carpaine carpaine alkaloid in this study was lower because of the geographical and climate differences in Indonesia and Vietnam, make the nutrients in the soil would be vary causing differences content of secondary metabolites.…”
Section: Discussioncontrasting
confidence: 53%
“…Papaya alkaloids have an anticoagulant activity that can prolong CT, PT, and aPTT times compared to controls. The total alkaloid content in papaya leaves is between 1.6% (23) and 1.8% (24) . Papaya leaf total alkaloids have antiplatelet, anticoagulant, and thrombolytic activity by increasing the percentage of inhibition of platelet aggregation, significantly prolonging CT, PT, and aPTT and increasing the percentage of thrombolytic (24) .PT increased significantly (p≤0.01) at a concentration of 100 gr and (p≤0.001) at a concentration of 300 and 600 gr, respectively.the effect of adding sample is similar to 1 mg of rivaroxaban.…”
Section: Carica Papaya Lmentioning
confidence: 99%
“…Berdasarkan kajian literatur, diketahui bahwa daun pepaya mengandung alkaloid, flavonoid, fenol, asam fenolik, kolin, karposit, vitamin C dan vitamin E [31]. Pada penelitian ini, kadar alkaloid total yang diperoleh adalah 1,8%, lebih banyak dibandingkan dengan penelitian terdahulu yang hanya memperoleh 0,2% kadar alkaloid total daun pepaya [32]. Kandungan alkaloid di dalam daun pepaya ini terdiri dari alkaloid jenis karpain, pseudokarpain, emetin dan dehidrokarpain I dan II [33].…”
Section: Hasil Dan Diskusiunclassified
“…Kandungan alkaloid di dalam daun pepaya ini terdiri dari alkaloid jenis karpain, pseudokarpain, emetin dan dehidrokarpain I dan II [33]. Analisis kuantitatif karpain daun pepaya yang dimurnikan dengan HPLC menunjukkan bahwa karpain merupakan alkaloid utama dengan kandungan 63% dari total alkaloid yang diekstrak dari daun pepaya [32].…”
Section: Hasil Dan Diskusiunclassified
See 1 more Smart Citation